Novel keto–enol tautomerism in 1, 3, 5-trihydroxybenzene systems. Issue 85 (30th September 2020) - Ruaysap, Makabodee; Kennedy, Stuart R.; Mayhan, Collin M.; Kelley, Steven P.; Kumari, Harshita; Deakyne, Carol A.; Atwood, Jerry L.
Abstract : We report a new synthesis of the water-soluble compound 1, 3, 5-trihydroxy-2, 4, 6-trimethylsulfonic acid (1), which exists in two tautomeric forms (60 : 40::enol%:keto%), and its lanthanide complexes. Relative tautomer stability is influenced by intramolecular H-bonding and competing implicit solvent effects. Abstract : We report a new synthesis of the water-soluble compound 1, 3, 5-trihydroxy-2, 4, 6-trimethylsulfonic acid (1), which exists in two tautomeric forms (60 : 40::enol%:keto%) and can be used as a proton conductor. Quantum chemical calculations show the importance of intramolecular hydrogen bonding and the presence of implicit MeOH solvent on the relative stabilities of the tautomers. 1 complexes with lanthanides through its sulfonato groups and forms a layered cage-like structure with one intramolecular and two intermolecular hydrogen bonds.